TEOLOGI HUMANIS DALAM PEMIKIRAN M. AMIN ABDULLAH - Jainul Arifin (UIN Sunan Kalijaga Yogyakarta, 2020)
Theology in this paper is interpreted as the relationship between religion and social reality that is captured by someone who adheres to it.In other words, a person's perspective in hugging, believes, and practice religion in the midst of social reality.While humanism is an understanding that upholds humanity or humanize humans.So how is the understanding of religion or the way of religion in the midst of a pluralistic social reality (theology) still sided with the humanists? This paper uses the method of studying the social context and orientation of humanism in the early modern era and the results are in reality, then linked with theology to be applied to contemporary plural social reality. The author uses the perspective of M. Amin Abdullah which is based on the epistemology of Irfani associated with the view of the World Community and Ethics in favor of human values. The result is that Irfani provides the basis for unity in differences orunity in diversity. Views of the World Community, irfani became the basis that everyone in all countries in the world should not identify himself as the most important and most prominent because the nation, religion, profession and race. Ethics is, because it is not just a normative prohibition but rather is the peak of the accumulation of one's intelligence operationalization ability or intelligence, then the concept of ethics (thinkers or philosophers or theologians) It is hoped that it can provide a creative basis for rules or morals that can favor universal human values.